Plant-Based Diets in Hispanic/Latino Adult Adventists in the United States and Their Association With Body Mass Index. Issue 6 (July 2019) - Jaceldo-Siegl, Karen; Estevez, Dennys; Fraser, Gary E; Hayes-Bautista, David E; Flores, Hector; Jordan, Michael; Singh, Pramil N.
Purpose: To characterize plant-based dietary practices and examine their relationship with body mass index (BMI) in Hispanic/Latino Seventh-day Adventists (SDA). Design: Cross-sectional analyses of data among Hispanics/Latinos in the Adventist Health Study-2 (AHS-2). Setting: The AHS-2 is a cohort of SDA adults (n = 96 592) in North America. Participants: A total of 3475 Hispanics/Latinos who provided demographic, dietary, anthropometric, and lifestyle data at enrollment. Measures: Plant-based dietary practices were determined from food frequency questionnaire; BMI, demographic, and lifestyle data were assessed by questionnaire. Analysis: In linear regression analysis, plant-based diets were modeled as dummy variables with nonvegetarian as the referent group and log(BMI) as the outcome adjusted for age, sex, education, exercise, nativity, alcohol use, smoking, and energy intake. Results: We identified 202 vegans, 664 vegetarians, 409 pesco-vegetarians, 227 semi-vegetarians, and 1973 nonvegetarians. Compared to the nonvegetarian referent (BMI = 27.50), estimated BMI were lower among vegans (23.58, P < .0001), vegetarians (25.24, P < .0001), pesco-vegetarians (26.36, P = .0002), and semi-vegetarians (26.69, P = .130). Other factors associated with lower BMI were being female ( P = .001), nativity (Mexico, P = .002; South America, P < .0001; Caribbean, P = .004), having a college degree or higher ( P = .01), exercise ( P < .0001), and never smoked ( P = .0006). Conclusion: Hispanic/Latino SDAs who consumed plant-based diets had lower BMI than nonvegetarians. The application of a plant-based diet as practiced by the Hispanic/Latino Adventists in this population may have public health impact on US Hispanic/Latinos.